Penicillium ulleungdoense sp. nov. from Ulleung Island in Korea - Doo-Ho Choi; Young-Hyun You; In-Seon Lee; Seung-Bum Hong; Tea-Yeol Jung; Jong-Guk Kim (Mycobiology, 2021)
In a study of the fungal diversity on Ulleung Island in Korea, three novel strains of Penicillium were isolated. Different sites on Ulleung Island were selected for collecting endophytic fungi, and three endophytic fungal strains showed unique morphological characteristics. DNA sequence of the internal transcribed spacer, β-tubulin, calmodulin, and RNA polymerase II second largest subunit regions of the strains were analyzed and they showed unique taxonomic position from the other species of Penicillium section Sclerotiora. The new strains were named Penicillium ulleungdoense sp. nov. As the novel endophytic Penicillium taxa were discovered in a unique environment, the data could be meaningful for understanding the geographical distribution of Ascomycetes on Ulleung Island.